Does the endowment of contributors make a difference in threshold public games? - Federica Alberti; Edward Cartwright (University of Kent, School of Economics, 2010)
We investigate experimentally whether the endowment of potential contributors changes the success rate of providing threshold public goods. We find a U shaped relationship in which the success rate is relatively high when the endowment is either relatively small or large. We also find an inverted U shaped relationship in terms of the variance of contributions. This suggests that people find it hardest to coordinate and provide threshold public goods when endowments are of intermediate size. By this we mean that the endowment is small enough that people do need to contribute relatively a lot to fund the good, but is also large enough that no one person is critical in providing the good. Coordinating is difficult in this case because there is an incentive to free ride and the possibility to do so creating a conflict of interest.
Keywords: C72; H41; 330; public good; threshold; endowment